Material flow cost accounting with multiple inefficiency factors and recycling - Stefan Dierkes; David Siepelmeyer (Schmalenbach Journal of Business Research (SBUR), 2025)
Sustainability management requires differentiated information on the environmental and economic consequences of material demand's increasing and decreasing factors. Material flow cost accounting fails to provide this information due to the common undifferentiated determination of realized costs of material and product losses and, therefore, the lack of a~production theoretical basis for cost planning. We develop a~material flow model considering the impacts of waste and reject as material demand increasing factors and reworking and recycling as material demand decreasing factors at the company, quantity center, and product unit levels. This enables designing a~material flow cost accounting system with specific cost information on the different factors at each level. We also analyze the consequences of the material distribution key and possible alternatives for allocating costs in material flow cost accounting. Finally, we discuss further development opportunities for this accounting system.
Keywords: Q56; 650; Material flow cost accounting; Material flow model; Recycling; Resource efficiency; Reworking; Sustainability management